The interplay of conditional NCAM-knockout and chronic unpredictable stress leads to increased aggression in mice. (November 2013) - Kohl, Christine; Riccio, Orbicia; Grosse, Jocelyn; Zanoletti, Olivia; Fournier, Céline; Klampfl, Stefanie M.; Schmidt, Mathias V.; Sandi, Carmen
Abstract The neural cell adhesion molecule (NCAM) is a key regulator of brain plasticity. Substantial evidence indicates that NCAM is down-regulated by exposure to sustained stress and chronic stress seems to lead to increased aggression. In addition, constitutional NCAM deletion in mice has been shown to lead to increased intermale aggression and altered emotionality Forebrain-specific postnatal NCAM knockout was previously shown to impair cognitive function, particularly when animals were exposed to subchronic stress, but the effects on emotional and social behavior remain unclear. In this study, we investigated the potential interplay of a forebrain-specific postnatal NCAM deletion and exposure to different lengths of repeated stress (i.e. subchronic: 14 days; chronic: 29 days) on aggressive and emotional behavior. Our results show that postnatal deletion of NCAM in the forebrain leads to increased aggression and altered emotionality depending on the duration of stress, whereas conditional NCAM knockout has no basal impact on these behaviors. These findings support the involvement of NCAM in the regulation of emotional and aggressive behaviors, suggesting that diminished NCAM expression might be a critical vulnerability factor for the development of these behavioral alterations under repeated exposure to stress.